THE SYNCRETIC SWING OF FAITH IN MADDOA: ISLAMIC AND BUGINESE THEOLOGICAL ASSIMILATION IN PINRANG'S HARVEST FESTIVAL OF INDONESIA - Santalia, Indo (European journal for philosophy of religion, 2024)
Expressions of gratitude to God or any divine deity varies in each community, and often evolves from simple acts to complex rituals across different traditions. One such ritual is the Maddoa tradition of Pinrang community, Indonesia, practiced prior to a planting season, as an expression of gratitude to Allah SWT, especially by those whose occupation is agriculture. This study examines how the maddoa' (traditional swing) ceremony reflects a blend of cultural practices and broader Islamic theological perspectives in Pinrang, Indonesia. The research aimed to understand the ceremony's role in shaping community cohesion and religious identity. A qualitative ethnographic approach was employed with data collected through observations and interviews with spiritual leaders and local farmers. The findings revealed that, rather than following the simple expressions of praise typically found in Islamic teachings, the community performs intricated, seven-day rituals that conclude with the erection and use of the maddoa swing after a successful harvest. Although this practice diverges from orthodox Islamic norms, it is embraced as a form of gratitude and cultural preservation. This implies that religion can be adaptable to accommodate local customs through reinterpretations of tradition ('urf) or via a theological debate. The study’s scope is limited to one community and may not reflect broader patterns. Future research could further explore how local traditions are influenced by subtle adaptations or eroded by extreme interpretations of religious practices.